Tpeak-to-Tend/QT is an independent predictor of early ventricular arrhythmias and arrhythmic death in anterior ST elevation myocardial infarction patients. Issue 6 (1st October 2016) - Mugnai, Giacomo; Benfari, Giovanni; Fede, Alfredo; Rossi, Andrea; Chierchia, Gian-Battista; Vassanelli, Francesca; Menegatti, Giuliana; Ribichini, Flavio Luciano
Abstract: Background: The aim of our study was to analyse the markers of transmural dispersion of ventricular repolarization, especially Tpeak-to-Tend and Tpeak-to-Tend /QT ratio, in patients with anterior ST elevation myocardial infarction on admission and to evaluate their association with in-hospital life-threatening arrhythmias and mortality. Methods and results: A total of 223 consecutive patients with anterior wall ST elevation myocardial infarction admitted to our Division of Cardiology between January 2010 and December 2012 were prospectively evaluated. A standard electrocardiogram was obtained on admission and then analysed. The primary end point was constituted by in-hospital ventricular arrhythmias and arrhythmic death. At univariate analysis heart rate (odds ratio = 1.03; 95% confidence intervals 1.006-1.05; p =0.001), maximal ST elevation (odds ratio =1.25; 95% confidence intervals 1.10–1.43; p =0.0001), QTc Bazett (odds ratio = 1.01; 95% confidence intervals 1.006–1.02; p =0.002), QT dispersion (odds ratio = 1.02; 95% confidence intervals 1.002–1.04; p =0.02) and both Tpeak-to-Tend and Tpeak-to-Tend/QT (odds ratio = 1.02; 95% confidence intervals 1.01–1.03; p <0.0001 and OR = 1.07; 95% confidence intervals 1.03–1.11; p <0.0001 respectively) were significantly associated with ventricular arrhythmias and arrhythmic mortality. Of note, Tpeak-to-Tend /QT remained a predictor of early ventricular arrhythmias and arrhythmic death (odds ratio = 1.04; 95% confidence intervals 1.003 – 1.10; p =0.03) independently from heart rate and maximal ST elevation. Receiver operating characteristic curve analysis showed that Tpeak-to-Tend /QT values <0.31 had a predictive negative value of 92% for the prediction of the composite outcome. Conclusions: Tpeak-to-Tend /QT was an independent predictor of early ventricular arrhythmias and arrhythmic mortality in patients with anterior ST elevation myocardial infarction. Especially, Tpeak-to-Tend /QT <0.31 may identify a subgroup of ST elevation myocardial infarction patients with low risk of early arrhythmias and arrhythmic death.